Esthetic perception regarding periodontal changes: a crosssectional study - Sassi, Maira Soares; Almeida, Aislan Pereira de; Coqueiro, Raildo Silva; de Brito Júnior, Rui Barbosa; Pithon, Matheus Melo (Brazilian Dental Science, 2020)
Objective: Facial appearance has become an important factor of social interaction. The perception of patients regarding the changes promoted by treatment has become a focus of study today. Thus, the proposal of the present study was to evaluate the esthetic perception of lay people regarding esthetic periodontal changes. Method: The total sample comprised 180 individuals divided into three different age groups (15-19, 35-44, and 65-74 years). Nine images with digital alterations in the gingival contour were used. One of the images served as an esthetic standard for the research (ideal image). The images were presented to the evaluators using slide show software (Microsoft PowerPoint 2013, Microsoft, California). Was used the Wilcoxon, Kruskal-Wallis and Mann-Whitney test. The level of significance was 5% (? = 0.05). Results: Statistical differences were found between the esthetic perception of different age groups. The sample was composed only of lay people of three different age groups, and it was evident that the younger age group has a more accurate perception regarding changes in the gingival contour. Conclusion: The changes in the gingival contour perceived as less attractive were the changes between the central incisors. The younger age group had a more accurate esthetic perception in this study. KEYWORDS Periodontics; Gingival esthetics; Perception; Esthetics.